DEVELOPMENT OF THE BIOECONOMY AS A PREREQUISITE FOR INCREASING THE COMPETITIVENESS OF THE NATIONAL ECONOMY IN INTERNATIONAL MARKETS - BILOUSKO, Tamila; BILOUSKO, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The large-scale invasion and active hostilities in our country led to huge losses and exacerbated the economic problems of forming a competitive economy successfully integrated into the world economic system. The need for modern business support and accelerated post-war recovery of the economy prompts the transformation of the economy, based on the successful experience of other countries. The article outlines the relevance of the orientation of the economy of Ukraine to the global trends of concepts of bio-economic development, which combines social, economic and ecological aspects of development to ensure the quality of life of the country’s population, minimize the impact on the environment, develop a circular economy and increase the efficiency and competitiveness of the economy. Methodical approaches to defining the essence and components of the bioeconomy and the evolution of its recognition as the most relevant for the preservation of biodiversity, the ecosystem, and high-quality, socially responsible development of society are considered. It is shown that the bioeconomy contributes to the development and introduction of biotechnologies, which makes it possible to diversify energy supply, efficiently use waste, produce new types of products, and form competitive advantages of the national economy on international markets. The need for a systemic approach to the introduction of the bioeconomy and the use of biotechnology has been proven, which includes the creation of integrative associations of science, production, the state and the private sector, which will ensure the necessary investments and innovative breakthroughs in various sectors of the economy. The need to develop the concept of bioeconomy and adopt the national plan for the development of bioeconomy as a priority program document, the introduction of which will contribute to the post-war recovery of Ukraine’s economy, is substantiated.